Improving efficiency of MEH-PPV/TiO2 solar cells by lithium salt modification - Barkhouse, D; Bishop, H; Henry, B; Webster, G; Burn, P; Assender, H (2010)
The modification of MEH-PPV/TiO2 photovoltaic devices with the lithium salt, Li[CF3SO2]2N, is shown to result in a 40% increase in both the short-circuit current and fill factor while not affecting the open-circuit voltage. The power conversion efficiency of the modified devices is 1.05% under 80 mW/cm2 simulated solar illumination, which is twice that of the control device without the salt and the highest reported to date for a polymer/TiO2 solar cell. The increased performance is attributed to a large improvement in the hole mobility of the MEH-PPV, as measured by space-charge-limited current measurements, in the presence of the lithium salt. Modification of the devices with LiClO4 is not as effective at improving device performance. Secondary ion mass spectroscopy measurements reveal that the poorer performance is due to a lower degree of Li diffusion into the polymer layer for LiClO4 than for Li[CF3SO2]2N. © 2010 Elsevier B.V. All rights reserved.